Pengembangan Multimedia Pembelajaran dengan Pendekatan Saintifik - Yogia Friska Mulyani; Henry Praherdhiono; Yerry Soepriyanto (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
This development aims to produce multimedia products with a valid scientific approach as an effective learning resource in science subjects, the nature of light. This research uses the development model of William W. Lee and Diana L. Owens, the development steps are analysis, design, development, implementation and evaluation. Based on the results of validation to media experts and material experts as well as field trials, multimedia with a scientific approach is declared valid and effective for use as a learning medium